EFEKTIVITAS WASTE MOTOR OIL PADA PLAT INTERCEPTOR SEBAGAI MEDIA PENURUNAN KEPEKATAN FLUE GAS VARIASI MOISTURE CONTENT MSW - Andrayuga, I Wayan; Winaya, I Nyoman Suprapta; Darma, I Wayan Arya; Tenaya, I Gusti Ngurah Putu; Pratama, I Putu Angga Yuda (Teknik Desain Mekanika, 2024)
Abstract This study aims to develop a flue gas capture device with an interceptor plate with waste motor oil (WMO) media to reduce the flue gas density and odor arising from the drying process of municipal solid waste (MSW) with varying moisture content. Smoke and water vapor generated from the drying process of MSW are caused by the evaporation of MC at 110°C. By-products generated from the drying process are odorless polluting gases such as carbon monoxide (CO), carbon dioxide (CO2), and methane (CH4), as well as odorous gases such as ammonia (NH3), and hydrogen sulfide (H2S), which are highly dependent on the fraction of MSW being dried and the MC contained therein. The interceptor plate is made in the form of a block measuring 1 m long, 0.12 m wide and 0.13 m high where the plate is arranged in a zigzag manner to inhibit the flow of gas fumes so that pollutant particles are captured and attached to the WMO media coated on the surface of the plate. MC in MSW was varied from 50% to 10% to see the level of flue gas formation produced and the effectiveness of capturing polluted gases for a test time duration of 5 minutes. The results of the investigation showed that a decrease in the percentage of flue gas occurred in each variation of moisture content given at 50% MC, namely NH3 from 56.50 ppm to 22.61 ppm, H2S from 6.9 ppm to 2.5 ppm. The effectiveness and efficiency of WMO media capture was measured to be most optimal in the 50% MC variation with 13.6% ash capture from the flue gas produced. Keywords: interceptor plate, smoke, odor, waste motor oil (WMO), effectiveness, efficiency